2013
DOI: 10.1007/s10495-012-0800-8
|View full text |Cite
|
Sign up to set email alerts
|

The anti-mitotic drug griseofulvin induces apoptosis of human germ cell tumor cells through a connexin 43-dependent molecular mechanism

Abstract: Griseofulvin, a widely used antifungal antimitotic drug has been proposed as an anti-tumoral treatment by way of in vitro experiments. Recently, in vivo demonstration of griseofulvin efficacy against multiple myeloma in mice argues for its potential as therapeutics for cancer. Nevertheless, the molecular mechanisms by which griseofulvin disrupts cancerous cell progression are far from being understood. In the present study, we found that griseofulvin inhibits human germ cell tumor cell growth through activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…In addition to the above-mentioned findings, we observed that Cx43 gene transfection alone partially inhibited tumor growth in mice. This result is consistent with previous reports that considered Cx43 as a tumor suppressor gene (31)(32)(33). However, it is clear that the inhibitory effect of Cx43 alone on tumor growth is extremely limited (31,33).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition to the above-mentioned findings, we observed that Cx43 gene transfection alone partially inhibited tumor growth in mice. This result is consistent with previous reports that considered Cx43 as a tumor suppressor gene (31)(32)(33). However, it is clear that the inhibitory effect of Cx43 alone on tumor growth is extremely limited (31,33).…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with previous reports that considered Cx43 as a tumor suppressor gene (31)(32)(33). However, it is clear that the inhibitory effect of Cx43 alone on tumor growth is extremely limited (31,33). Similarly, the killing effect of HSVtk/GCV alone on liver cancer cells is limited, particularly in CD133 + cell spheres that were cultured in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…These results indicate that Cx43 is effective in enhancing the cytotoxicity of DTX by downregulating Bcl-2. Cx43 also aids in the apoptotic effects of germ cell tumors in response to Griseofulvin, an antifungal antimitotic drug, through translocation from the cytoplasm to the nucleus [23]. Cx43 immunoreactive signal was mainly found distributed throughout the cytoplasm of tumoral germ cells and there was no coupling found between adjacent cells.…”
Section: Cx43mentioning
confidence: 99%
“…In combination with Docetaxel, inhibits cell growth and induces apoptosis Mauro et al [23] JKT-1 cells Cx43…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation